PENGARUH STRATEGI ORGANISASI, INVESTASI ASET TETAP, DAN KINERJA PERUSAHAAN TERHADAP KUALITAS LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS MANUFAKTUR YANG TERDAFTAR DI BEI) - Rahayu Amalia Pertiwi; Hasnawati Hasnawati; Vinola Herawaty (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The purpose of this study was to examine the influence of organization's strategy, fixed asset investment, and firm performance on quality. In addition, testing whether organizational strategy, fixed asset investment, and company performance can moderate company size to earnings quality.This research uses moderate regression hypothesis testing. Sampling data taken from manufacturing companies listed on the Indonesia Stock Exchange during the year 2013-2016 which is 72 companies by using purposive sampling technique. The result of the research shows that the variable cost leadhership strategy, defferentation strategy and fixed asset investment have no effect on earnings quality, while the profitability variable using firm size variables express firm size strengthening relationship between cost lead strategy strategy, defferentation strategy and profitability to earnings quality.